Molecular characterization of mcr-1.1-harboring multidrug-resistant Escherichia coli isolates from chicken in the United Arab Emirates: implications for one health surveillance - Khalifa, Hazim O.; Elbediwi, Mohammed; Mohammed, Temesgen; Abdalla, Afra; Mohamed, Mohamed-Yousif Ibrahim; Lakshmi, Glindya Bhagya; Habib, Ihab (Frontiers in Veterinary Science, 2026)
BackgroundThe mcr-1.1 gene, conferring resistance to colistin, is a significant threat to public health, particularly due to its capacity for horizontal gene transfer between diverse bacterial populations in humans, animals, and the food chain. This study investigated the occurrence, phenotypic antimicrobial resistance (AMR) profiles, genetic characteristics, and plasmid characterization of mcr-1.1-producing Escherichia coli isolates from different samples in the United Arab Emirates (UAE).MethodsA total of 333 Gram-negative isolates were screened by PCR for the detection of mcr genes. Antimicrobial susceptibility testing, whole genome sequencing (WGS), plasmid analysis, and Phylogenomic typing were performed to assess AMR determinants, plasmid replicons, genetic contexts of mcr-1.1, and genetic relatedness between isolates from the UAE and neighboring countries.ResultsWe identified 15 mcr-1.1-positive E. coli strains, all from chicken cecal samples. These isolates exhibited multidrug resistance (MDR) to various classes of antibiotics, including β-lactams, tetracyclines, quinolones, and aminoglycosides. WGS of 15 mcr-positive E. coli isolates revealed the presence of multiple AMR genes along with mutations in quinolone resistance genes (gyrA, parC). Plasmid analysis revealed that all mcr-1.1-positive strains carried at least one plasmid replicon, with the IncF and IncI plasmids being the most prevalent. Notably, the mcr-1.1 gene was located on IncI2 and IncX4 plasmids, with comparative analysis showing high sequence homology to plasmids from E. coli strains originating from humans and animals in multiple countries. The plasmids’ high sequence homology across diverse geographical regions provides genomic evidence consistent with possible cross-border dissemination of mcr-1.1, facilitating the spread of colistin resistance. Genetic mapping of the mcr-1.1 gene revealed distinct genetic contexts depending on the plasmid type, with genes such as nikA, nikB, and pap2 flanking the gene on IncI2 and IncX4 plasmids. Clonal analysis using whole-genome sequencing identified 12 different sequence types (STs) among the 15 isolates, with ST10, ST117, and ST162 being the most prevalent. Core genome multilocus sequence typing demonstrated genetic relatedness between isolates from the United Arab Emirates (UAE) and neighboring countries, indicating potential transmission across borders via the food chain.ConclusionOur findings highlight the complex interaction between plasmid-mediated colistin resistance, AMR, and virulence traits in E. coli from the food chain. The genetic and plasmid similarities between mcr-1.1-producing isolates across multiple countries emphasize the risk of possible dissemination and the potential risk of cross-border dissemination through globally traded food products. This study underscores the need for regional and global surveillance and control measures to mitigate the spread of this multidrug-resistant pathogen.